Determinants of early-stage technology venture valuation by business angels and venture capitalists. (5th September 2019) - Wessendorf, Christoph Philipp; Kegelmann, Jens; Terzidis, Orestis
The valuation of early-stage ventures represents a difficult and often subjective process and is characterised by risk and uncertainty. This can be further stressed for technology-driven ventures, having substantial technological risks. We therefore approached existing research on the determinants of early-stage technology venture valuation in a structured way through means of a systematic literature review (SLR). Whereas general valuation determinants strongly focus on personality and experience of the founders as well as market potential, technology venture valuation is strongly influenced by the existence and quality of alliances with corporations and investors as well as patents. We consider these determinants as crucial in technology venture valuation to ensure market access, to signal a strong belief in the technology and to provide proof of a high degree of innovation, thereby noticeably reducing technology-specific complexity and uncertainty.